People and protected areas - Kothari, Ashish (ed.); Singh, Neena (ed.); Suri , Saloni (ed.) (New Delhi, 1996)
Conflicts between rural communities and wildlife conservationists have become commonplace in India. This volume explores ways to understand and resolve these conflicts. The contributors focus primarily on India's vast network of national parks and sanctuaries. Among the themes discussed are: participatory management of protected areas; the legal and policy implications of participatory management; and the institutional and procedural aspects involved in new strategies of joint management. There are case studies of a number of sanctuaries within India and an overview of similar efforts across the globe.
Keywords: Nature conservation